Tolerance, Growth, and Physiological Responses of the Juvenile Razor Clam (Sinonovacula constricta) to Environmental Ca(2+) and Mg(2+) Concentrations - Peng, Maoxiao (Front Physiol, 2019)
To facilitate transplanting razor clam (Sinonovacula constricta) populations to inland saline-alkaline waters (ISWs), we evaluated the tolerance of juvenile S. constricta (JSC) to Ca(2+) and Mg(2+) concentrations, and determined the effects of these ions on JSC growth and physiological parameters. After 30 days stress, the tolerable ranges of JSC to Ca(2+) and Mg(2+) were determined to be 0.19 mmol⋅L(-1)–19.46 mmol⋅L(-1) and 0 mmol⋅L(-1)–29.54 mmol⋅L(-1), respectively. The concentrations of Ca(2+) (less than 0.65 mmol⋅L(-1) or more than 3.24 mmol⋅L(-1)) and Mg(2+) (less than 0.37 mmol⋅L(-1) or more than 14.17 mmol⋅L(-1)) significantly inhibit JSC growth. Physiological enzyme activity no significant response when the concentrations range of Ca(2+) and Mg(2+) are 0.93 mmol⋅L(-1)–6.49 mmol⋅L(-1) and 0.37 mmol⋅L(-1)–14.77 mmol⋅L(-1), respectively. For transplantation practice, these data indicate that only high concentrations of Ca(2+) (3.24–6.825 mmol⋅L(-1)) and Mg(2+) (14.77–33.69 mmol⋅L(-1)) in target inland saline-alkaline water had significantly impact on growth and physiological response. In addition, present study suggests that the increase in Ca(2+) and Mg(2+) ion concentrations caused by ocean acidification will not affect the survival, growth and physiology of S. constricta. Current research suggests that S. constricta can adapt to extreme changes in the marine environment (Ca(2+) and Mg(2+)) and may be an excellent candidate for inland saline-alkaline water transplantation practice.